Faktor-Faktor Yang Mempengaruhi Kualitas Hidup Penderita HIV/AIDS Di Kabupaten Boyolali Dan Kota Surakarta (Solo) Provinsi Jawa Tengah Tahun 2012 - , Nova Oktavia ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Human immunodeficiency virus or HIV is a virus that attacks the immune system. There is no province in Indonesia is free from HIV and AIDS. Cases of HIV / AIDS in Central Java, 1993-September 2011 amounted to 4299, died at CFR 555 (29.23%). The purpose of research comparing domain scores and significant differences quality of life of HIV/AIDS based on socio-demographic and related HIV infection factors Methods: Cross sectional survey study was carried out using consecutive sampling method on 32 patients living with HIV. The independent variables were the factors that affect the quality of life of people living with HIV. The dependent variable is the quality of life (physical, psychological, independence, social, environmental and spiritual domain). The research instrument used WHOQOLHIV- Bref and structured questionnaire. Results: A significant difference was observed with respects to: the occupation in the physical, independence, social, environment and spiritual domain